Development of strategic pitching skill items in professional baseball games - Tahara, Y.; Matsuoka, H.; Hato, K.; Nishijima, T. (Journal of Physical Education and Sport, 2025)
Introduction: Strategic decision-making in pitching is a crucial factor in baseball performance, yet traditional metrics like earned run average and even advanced sabermetrics such as fielding independent pitching (FIP) and strikeout-to-walk ratio (K/BB) fail to directly measure how pitchers adapt their pitch selection in response to situational demands. Relatedly, although sports science has explored biomechanical and physiological aspects of pitching, little attention has been paid to the intentional structure of pitching strategy. This study addresses this critical gap by developing and validating a measurement model of strategic pitching skills based on pitch-by pitch data. Materials and Methods: Using data from Nippon Professional Baseball (NPB), the study analyzed 28,222 plate appearances. A causal-effect analysis with the Delphi method was conducted with expert input to define two main domains of strategic pitching skill: pitch velocity skill and pitch location skill. Sub-skills included off-speed variation (velocity) and vertical, horizontal, and diagonal skills. A total of 20 items were initially created based on differences in pitch characteristics relative to the context (e.g., pitch count, previous pitch). Exploratory and confirmatory factor analyses were conducted to test the construct validity, followed by structural equation modeling (SEM) to examine criterion-related validity using FIP and K/BB as external indicators. Results and Discussion: After the exploratory analysis, 18 items remained, yielding a four-factor model that explained 70% of the variance. A confirmatory factor analysis further supported this model, and both horizontal and off-speed skills showed significant associations with improved performance, reflected in lower FIP (-0.51 and -0.39, respectively) and higher K/BB (0.76 for horizontal skill). These results confirm that the developed items are not only statistically valid but also practically meaningful. This model provides a novel framework for evaluating strategic pitching skills and has potential applications in individualized coaching, performance analysis, and AI-based scouting systems. Conclusions: This study developed and validated a set of strategic pitching skill items based on pitch-by-pitch data from NPB. The resulting model consists of two domains—pitch velocity skill and pitch location skill—comprising four sub-skills. Construct and criterion related validity were confirmed, particularly for horizontal and off-speed skills. These skills offer practical value as measurable indicators for coaching, scouting, and player development.